Implementation of Exemplary-Based Moral Education in the Development of Students at Islamic Boarding Schools - Halimatuzzahrah Halimatuzzahrah; Eva Zulfa; Muhammad Zulfahmi Akbar (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2026)
This study aims to analyze the implementation of exemplary-based moral education in the development of students at Pondok Pesantren Al-Istiqomah Kapu. The study is motivated by the challenges faced by Islamic boarding schools in maintaining students’ moral development amid increasingly complex social and technological changes. The focus of the research is directed toward the forms of exemplary implementation, the supporting and inhibiting factors, and its influence on students’ behavior in their daily lives. This study employed a qualitative approach with a field research design. Data were collected through participatory observation, in-depth interviews, and documentation involving the head of the boarding school, teachers, dormitory administrators, and students as research informants. The data were analyzed interactively through the stages of data reduction, data display, and conclusion drawing. The findings reveal that exemplary-based moral education is implemented through the habituation of daily behaviors directly demonstrated by teachers and dormitory administrators, such as discipline in congregational prayers, the use of polite language, responsibility, and concern for the cleanliness of the boarding school environment. The study also found that exemplary behavior has a positive influence on students’ character formation, particularly in the aspects of discipline, respectfulness, and social responsibility. However, the implementation of moral education still faces several obstacles, including the influence of social media, differences in students’ backgrounds, and limited supervision. This study concludes that exemplary conduct plays an important role in strengthening moral education in Islamic boarding schools because moral values are more easily internalized through real practices and daily interactions.